THE EFFECTIVENESS OF THE FLIPPED CLASSROOM TECHNOLOGY IN TEACHING DATABASE COURSES IN HIGHER EDUCATION - Inobat G`aniyeva; Isomiddinov Ma`rufjon (TADQIQOTLAR, 2025)
Abstract This  paper  explores  the  effectiveness  of  the  Flipped  Classroom  model  in teaching Database courses within higher education. The study aims to determine how the  integration  of  digital  learning  environments  and  active  learning  strategies influences students’ academic performance, engagement, and digital competence. The research  was  conducted  at  Qarshi  State Technical  University,  where  students  were divided  into  control  and  experimental  groups.  The  experimental  group  received instruction  through  the  Flipped  Classroom  model,  which  combines  pre-class  video lectures and in-class collaborative problem-solving activities. The results revealed a significant improvement in students’ understanding of database concepts, motivation, and participation compared to the traditional teaching approach. The study concludes that the Flipped Classroom approach enhances digital competence and improves the overall learning outcomes in database education.